Toba Community Perceptions of Education, Tourism, Health, and Socio-Religious Issues in Lake Toba - Siregar, Ameilia Zuliyanti; Sagala, Raihan Azhari (Piramida Akademi, 2025)
Toba Regency is one of the leading of local and foreign tourists destinations in North Sumatra Province. Through good management by the government, the private sector, and the community, this potential can be optimized to improve community welfare. This study aims to measure and evaluate the level of satisfaction of the tourists with the quality of life in various fields of education, tourism, health, agriculture, socio-culture-art, and religion. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 30 randomly selected respondents in the Toba region. The results show that improving the quality of education through curriculum development, increasing the capacity of teachers, and providing adequate facilities is very important. Community-based tourism development and infrastructure improvements can boost the local economy. In the health sector, improving access and quality of health services through community-based programs is necessary. Agricultural productivity can be improved through the application of modern technology and crop diversification. In addition, the preservation of local culture and arts as well as improved religious facilities and programs can strengthen social cohesion and the spiritual well-being of the community. This research is expected to provide a comprehensive picture of the quality of life of the Toba people and form the basis for formulating more effective policies to improve the quality of life of the community